TLR7 rs179008 (A/T) and TLR7 rs3853839 (C/G) polymorphisms are associated with variations in IFN-α levels in HTLV-1 infection - Santana, Emmanuelle Giuliana Mendes; Ferreira, Fabiane dos Santos; Brito, Wandrey Roberto dos Santos; Lopes, Felipe Teixeira; de Lima, Aline Cecy Rocha; Neto, Gabriel dos Santos Pereira; Amoras, Ednelza da Silva Graça; Lima, Sandra Souza; da Costa, Carlos Araujo; Souza, Maísa Silva; Ishak, Ricardo; Cayres-Vallinoto, Izaura Maria Vieira; et al. (Frontiers in Immunology, 2024)
IntroductionTLR7 detects the presence of single-stranded RNA (ssRNA) viruses, including human T-lymphotropic virus 1 (HTLV-1), and triggers antiviral and inflammatory responses that are responsible for infection control. Genetic variations in the TLR7 gene may alter cytokine production and influence the course of HTLV-1 infection. In the present study, the associations of TLR7 gene polymorphisms with HTLV-1-related symptoms, receptor expression levels, IFN-α and TNF-α levels and the proviral load were investigated.MethodsBlood samples from 159 individuals with HTLV-1 infection (66 with inflammatory diseases and 93 asymptomatic individuals) and 159 controls were collected. The genotyping of polymorphisms, TLR7 gene expression analysis and the quantification of the proviral load were performed by real-time PCR, and cytokine measurement was performed by enzyme-linked immunosorbent assay (ELISA).ResultsCarriers of the polymorphic allele for TLR7 rs179008 (A/T) had lower levels of IFN-α, while carriers of the polymorphic allele for TLR7 rs3853839 (C/G) had higher levels of TLR7 and IFN-α expression. The polymorphisms were not associated with symptoms of diseases related to HTLV-1 infection. The combination of A/G alleles for the TLR7 rs179008 (A/T) and TLR7 rs3853839 (C/G) polymorphisms was associated with increased IFN-α levels and a decreased proviral load.DiscussionAlthough the polymorphisms did not influence the presence of symptoms of diseases caused by HTLV-1, carriers of the wild-type alleles for TLR7 rs179008 (A/T) and the polymorphism for TLR7 rs3853839 (C/G) appears to have a stronger antiviral response and increased infection control.